Implementasi Program Dana Bantuan Operasional Sekolah (Bos) Sekolah Menengah Pertama Di Kabupaten Padang Lawas - Putra Aulia Ramadhan; Siti Hazzah Nur (AL-Ikhtiar : Jurnal Studi Islam, 2025)
The high number of children who do not continue their education to junior high school (SMP) due to limited facilities, especially in remote areas, is a serious problem in Padang Lawas Regency. The School Operational Assistance (BOS) program, which is expected to support equitable distribution of educational services, is deemed suboptimal. This study aims to describe the implementation of the BOS program at the junior high school level in Padang Lawas Regency. The study used qualitative methods with a descriptive approach. Data were obtained through interviews, observations, literature studies, and secondary data. The analysis was based on policy implementation indicators according to Charles O. Jones (1996), which include organization, interpretation, and application. The research informants included officials from the Education and Culture Office, school principals, community leaders, and dropouts. The results indicate that the organization of the BOS program is suboptimal due to the lack of regional regulations, such as Regent Regulations, that adapt central policies to local conditions. In terms of interpretation, the use of BOS funds does not fully reflect social, economic, and geographic needs, for example, the purchase of technology in areas with unstable electricity, while basic infrastructure is neglected. In terms of implementation, despite the budget increase, the impact on education quality has not been significant. The allocation model based on student numbers results in small schools in remote areas receiving minimal funding, despite their greater needs. Abstrak Tingginya angka anak yang tidak melanjutkan pendidikan ke jenjang Sekolah Menengah Pertama (SMP) akibat keterbatasan fasilitas, terutama di wilayah terpencil, menjadi permasalahan serius di Kabupaten Padang Lawas. Program Dana Bantuan Operasional Sekolah (BOS) yang diharapkan mampu mendukung pemerataan layanan pendidikan dinilai belum optimal. Penelitian ini bertujuan untuk mendeskripsikan implementasi Program Dana BOS tingkat SMP di Kabupaten Padang Lawas. Penelitian menggunakan metode kualitatif dengan pendekatan deskriptif. Data diperoleh melalui wawancara, observasi, studi pustaka, dan data sekunder. Analisis didasarkan pada indikator implementasi kebijakan menurut Charles O. Jones (1996) yang meliputi pengorganisasian, interpretasi, serta penerapan/aplikasi. Informan penelitian terdiri dari pejabat Dinas Pendidikan dan Kebudayaan, kepala sekolah, tokoh masyarakat, serta anak-anak putus sekolah. Hasil penelitian menunjukkan bahwa pengorganisasian Program BOS belum optimal karena ketiadaan regulasi daerah seperti Peraturan Bupati yang mampu menyesuaikan kebijakan pusat dengan kondisi lokal. Pada aspek interpretasi, penggunaan dana BOS belum sepenuhnya mencerminkan kebutuhan sosial, ekonomi, dan geografis, misalnya pembelian teknologi di daerah dengan listrik tidak stabil, sementara sarana dasar terabaikan. Dari sisi penerapan, meskipun anggaran meningkat, dampaknya terhadap mutu pendidikan belum signifikan. Pola alokasi berbasis jumlah siswa menyebabkan sekolah kecil di daerah terpencil menerima dana minim, padahal kebutuhan mereka lebih besar.